2019
DOI: 10.1080/10749357.2019.1683792
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on user acceptance of a home-based stroke telerehabilitation system

Abstract: A qualitative study on a home-based stroke telerehabilitation system Objective: This paper reports a qualitative study of a home-based stroke telerehabilitation system. The telerehabilitation system delivers treatment sessions in the form of daily guided rehabilitation games, exercises, and stroke education in the patient's home. The aims of the current report are to investigate patient perceived benefits of and barriers to using the telerehabilitation system at home. Methods: We used a qualitative study desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
117
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(124 citation statements)
references
References 16 publications
2
117
0
5
Order By: Relevance
“…Stroke telerehabilitation programs involving consultations, exercises, games, and therapy aspects have shown positive outcomes such as improving patients' functional abilities and mental health (4). Other benefits include increasing patient motivation and ease due to being in a home setting (73). It is important that patients receive enough support in areas such as technical setup and troubleshooting.…”
Section: Telemedicine-assisted Follow-up and Rehabilitationmentioning
confidence: 99%
“…Stroke telerehabilitation programs involving consultations, exercises, games, and therapy aspects have shown positive outcomes such as improving patients' functional abilities and mental health (4). Other benefits include increasing patient motivation and ease due to being in a home setting (73). It is important that patients receive enough support in areas such as technical setup and troubleshooting.…”
Section: Telemedicine-assisted Follow-up and Rehabilitationmentioning
confidence: 99%
“…Satisfaction is another important indicator of the efficacy of therapeutic interventions. A high level of satisfaction promotes the patient's motivation to engage in rehabilitation ( Chen et al, 2020 ; Piron et al, 2008 ).…”
Section: Review Results and Discussionmentioning
confidence: 99%
“…We hypothesize that this was because the device allowed the patient to feel free to perform the rehabilitation session as desired, both in terms of time and place. Also, the study of Chen et al 45 highlighted how devices for telerehabilitation should be designed in order to offer an engaging experience with display of recovery progress and flexibility in schedule and location. Although, Knepley et al 46 showed in their review that there was no consistent evidence to support that telerehabilitation was better than face-to-face rehabilitation, they underlined that it had several advantages, like increased patient satisfaction through interactive video exercises, familiar location and feasibility, allowing telerehabilitation to become a valuable alternative for vulnerable patients.…”
Section: Discussionmentioning
confidence: 99%
“… 23 These groups could benefit from a system that allows a health professional to provide rehabilitation services from a remote location. 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation